PENGEMBANGAN MODUL PEMBELAJARAN BERORIENTASI PROBLEM BASED LEARNING MATERI PERMASALAHAN SOSIAL DI SEKITAR KITA KELAS V SD - Delta Rani Reangraini, Delta Rani (Sublim: Jurnal Pendidikan, 2023)
AbstractThe problem in this research is that student learning outcomes on social problems around us are still relatively low. The aim of the research is to see the potential development of the results of the development of problem based learning oriented learning modules on social problems around us in class V elementary school. This research is a type of research and development (R&D) research. This researcher uses the ADDIE model which consists of (Analyze, Design, Development, Implementation, and Evaluation) validation results on problem based learning oriented learning modules on social problems around us in class V by validators declared "Very Valid". Mrs. Dian Mayasyari, S.Pd's validation results were 99.04% "very valid". From the results of the One To One Evaluation trial, it was found that 90.55% was "very practical". From the results of the Small Group Evaluation trial, it was obtained that 96.45% was "very practical". Keywords: ADDIE, Module, Problem Based Learning, Social Problems Around Us Abstrak Masalah dalam penelitian ini yaitu hasil belajar siswa pada materi permasalahan sosial di sekitar kita masih tergolong rendah. tujuan penelitian yaitu untuk melihat pengembangan potensial dari hasil pengembangan modul pembelajaran berorientasi problem based learning materi permasalahan sosial di sekitar kita kelas V SD. Penelitian ini merupakan jenil penelitian research and development (R&D) peneliti ini menggunakan model ADDIE yang terdiri dari (Analyze, Design, Development, Implementation, Dan Evaluation) hasil validasi pada modul pembelajaran berorientasi problem based learning materi permasalahan sosial di sekitar kita kelas V oleh validator di nyatakan “Sangar Valid”. hasil validasi ibu dian mayasyari, S.Pd sebesar 99.04 % “sangat valid”. Dari hasil uji coba One To One Evaluation di peroleh 90,55% “sangat praktis” Dari hasil uji coba Small Groub Evaluation ini di peroleh 96,45% “sangat praktis”. Kata Kunci: ADDIE, Modul, Problem Based Learning, Permasalahan Sosial Di Sekitar Kita